ANALISIS KUALITAS SOAL BAHASA INDONESIA BERBASIS TAKSONOMI BLOOM REVISI PADA PLATFORM QUIZIZZ UNTUK PESERTA DIDIK SMP - Nufus, Hayatun; Sulistia, Rika; Ratna Dewi, Agis; Yaro, Hairo; Puspitasari, Rahma; Hati, Tiara; Dina Setiawati, Aisya; Natania Putri Marina, Nabila; Rama Dani, Alya; Putri Ramadani, Olivia; Riska; Aulia Riani, Ririn; Indah Sari, Fadilah; Robiah; Wulandari, Putri; Ceca Olivia, Sesilia; Natasya, Putri; Aprilia, Winsi; Anggraini, Imelda; Utami, Faza; Agustina, Gita; Anisa, Fitri; Pratiwi, Adelia; Pernando, Jimi; Salsabilah; Sulastri, Tera; Sundari, Meila; Gala Aprilia, Irsya; Iles Pahmi, Riken (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Revised Bloom’s Taxonomy developed by Anderson and Krathwohl (2001) classifies cognitive processes into six hierarchical levels from C1 (remembering) to C6 (creating), divided into lower-order thinking skills (LOTS) and higher-order thinking skills (HOTS). The problem underlying this study was the lack of adequate examination of Indonesian language question quality on digital learning platforms based on the Revised Bloom’s Taxonomy, leaving the extent to which these items measure students’ thinking skills uncertain. This study aimed to analyze the quality of Indonesian language test items on the Quizizz platform based on the cognitive levels of the Revised Bloom’s Taxonomy. A descriptive qualitative approach with content analysis method was applied to 40 multiple-choice Indonesian language test items for junior high school level, collected through documentation techniques and classified into C1–C6 levels and knowledge dimensions of the Revised Bloom’s Taxonomy. The results showed that cognitive level distribution was dominated by C2 (understanding) at 37.5% and C4 (analyzing) at 32.5%, while C1 (remembering) appeared only at 2.5%. The LOTS and HOTS proportion achieved a balanced ratio of 50:50, exceeding the minimum standard set by the Ministry of Education. In terms of knowledge dimension, items were dominated by conceptual knowledge (32.5%) and procedural knowledge (30.0%), while factual knowledge had the lowest percentage (17.5%). However, C3 (applying) representation remained low at 10.0%, indicating that the cognitive ladder from C1 to C6 has not yet been built in a fully gradual manner. It is concluded that the quality of Indonesian language test items on the Quizizz platform aligns with the Revised Bloom’s Taxonomy in terms of LOTS-HOTS balance, although the distribution across cognitive levels, particularly C3, still requires improvement.